Effect of gender and slaughter conditions on pH decline and proteolysis of ostrich meat during ageing by SDS-PAGE - H. Baghaei; M.J. Varidi; Mehdi Varidi; Z. Es´haghi (Pizhūhish va Nuāvarī dar ̒Ulūm va Sanāyi̒-i Ghaz̠āyī, 2013)
Postmortem proteolysis is one of the best ways to study meat tenderizing process. In this research, two groups of ostriches (male and female) were slaughtered by two methods: commercial (without electrical shock) and noncommercial (by electrical shock at 80 v/ 500 mA/ 10 s). pH decline of M. Gastrocnemius pars externa muscle was measured at 0, 1, 3, 6, 9, 18 and 24 hours and 3, 5, 7, 14 days during aging. Myofibrillar protein changes were evaluated at 1, 3, 5, 7 and 14 days postmortem by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). Results showed that electrical stunning accelerated glycolysis rate especially at 1 to 3 hours postmortem (P<0.05). Female ostriches had faster pH decline (P<0.05). Myofibrillar patterns indicated that major changes was corresponded to the gradual degradation of troponin T from day 1 onwards and simultaneously appearance of 25 to 32 KDa peptides (P<0.05). Myosin Heavy Chain (MHC), α-actinin and desmin were degraded during storage period and polypeptides of 60 and 100 KDa were observed at this time. Because of accelerated pH decline, gender and slaughter conditions had significant effect (P<0.05) on degradation of most proteins that were substrates for calpaein enzymes.